Highly viscous anti-skid wear-resistant steel slag cold-mixed asphalt wearing layer mixture and preparation method thereof
Patent Information
- Application Number
- CN202512051289.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-31
- Publication Date
- 2026-10-27
AI Technical Summary
但该专利仅从固废材料角度通过水化胶凝反应来提升对骨料的粘附性,性能提升更聚焦于沥青胶浆,与等量添加普通硅酸盐水泥的常规技术手段有等效作用;而硅烷偶联剂的使用更多是有机与无机材料的界面桥接,未能从实质上提升界面粘结强度,作用效果有限,且整个技术体系缺乏针对钢渣骨料与天然骨料因密度、孔隙差异导致的油石比设计合理性问题的考虑
[0028](1)本发明采用具有高耐磨、高强度、棱角性优等特性的钢渣骨料作为冷铺抗滑磨耗层的骨架结构材料,可以显著提升磨耗层的耐磨性。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This invention belongs to the field of road paving materials technology, specifically relating to a high-viscosity, anti-skid, and wear-resistant steel slag cold-mix asphalt wear layer mixture and its preparation method. Background Technology
[0002] When asphalt pavements are in good overall condition but have already shown minor defects, preventative maintenance techniques can effectively slow down the rate of performance degradation and extend their service life. Mainstream preventative maintenance technologies such as slurry seal, Cape seal, and micro-surfacing are widely used in asphalt pavement maintenance projects due to their significant advantages, including energy saving, excellent workability of the mixture, low environmental pollution, short construction period, and ability to be applied at normal temperatures. However, due to multiple limitations in materials and processes, under the repeated shear stress and impact loads of traffic loads during actual service, defects such as aggregate loss and delamination from the base surface are easily observed. Simultaneously, due to insufficient adhesion and limited aggregate wear resistance, the pavement's skid resistance rapidly declines after a short period of use. The wear resistance and skid resistance durability are insufficient to meet the requirements of heavy traffic or long longitudinal slope sections, ultimately affecting pavement smoothness, driving safety, and service life. For example, Chinese patent CN117623677A discloses a cold-laid anti-skid wear layer material and its preparation method, comprising the following raw materials in parts by weight: 9-11 parts modified emulsified asphalt, 65-75 parts steel slag aggregate, 6-9 parts synthetic micro powder, 4.5-7 parts modified material, and 0-6 parts water. The mixture of this invention uses steel slag aggregate modified with a silane coupling agent to improve the wear resistance of the pavement wear layer, uses synthetic micro powder composed of carbide slag, red mud, and desulfurization ash to improve the adhesion between asphalt and steel slag aggregate, and introduces two types of plasticizers to reduce asphalt aging problems, resulting in a cold-laid anti-skid wear layer material with strong adhesion, good high-temperature stability, and significantly improved oil separation phenomenon. However, this patent only improves the adhesion to aggregates through hydration and gelation reactions from the perspective of solid waste materials. The performance improvement is more focused on the asphalt binder, which has an equivalent effect to conventional techniques that add an equal amount of ordinary silicate cement. The use of silane coupling agents is more about bridging the interface between organic and inorganic materials, and fails to substantially improve the interfacial bonding strength, so the effect is limited. Moreover, the entire technical system lacks consideration for the rationality of the asphalt-aggregate ratio design caused by the difference in density and porosity between steel slag aggregate and natural aggregate. Based on this, the present invention provides a high-viscosity, anti-slip, and wear-resistant cold-mix asphalt wear course mixture with steel slag. Summary of the Invention
[0003] In view of the shortcomings of the prior art, one of the objectives of this invention is to provide a high-viscosity, anti-skid, and wear-resistant steel slag cold-mix asphalt wear course mixture. This invention achieves high viscosity and high wear resistance of the wear course by optimizing materials and mix proportions, which can effectively repair micro-diseases on the road surface, while improving the anti-skid performance of the road and ensuring driving comfort and safety.
[0004] To achieve the above objectives, the specific technical solution of the present invention is as follows:
[0005] A high-viscosity, anti-slip, and wear-resistant steel slag cold-mix asphalt wear course mixture comprises the following components in parts by weight: 8-11 parts modified emulsified asphalt, 35-55 parts steel slag aggregate, 30-50 parts manufactured sand, 6-9 parts activated micro powder, 6-10 parts thickening and modifying material, 0.3-1.5 parts hybrid flocculant component, and 5-8 parts water;
[0006] The tackifying and modifying materials include epoxy resin, ketimine, diethylenetriamine, tartaric acid, citric acid, T-31 curing agent, ethanol, Schiff base, and trimethylbenzylammonium hydroxide.
[0007] This invention uses steel slag aggregate, which has high wear resistance, high strength, and excellent angularity, as the skeleton structural material of the cold-laid anti-slip wear layer, which can significantly improve the wear resistance of the wear layer.
[0008] In traditional cold-mix slurry mixtures such as micro-surfacing and slurry seal, fillers smaller than 0.075mm are mainly used to bond with asphalt to form a mortar, playing a physical filling role. To further improve the wear resistance and high-temperature stability of the wear course mixture, this invention eliminates fine powder smaller than 0.075mm from the manufactured sand and replaces it entirely with steel slag-based active micro-powder. Without altering the aggregate gradation curve, this active micro-powder undergoes a hydration reaction with water to generate hydration cementitious products, which can improve the microstructure and interfacial deformation of the mixture mortar. Together with asphalt and aggregates, it forms a more rigid three-dimensional skeletal network structure, effectively improving the mixture's resistance to spalling, wear, and water loss.
[0009] The strength formation mechanism of traditional slurry mixtures using emulsified asphalt as the binder involves the emulsified asphalt being adsorbed onto the aggregate surface, bonding the entire mixture together. This process is accompanied by water seepage, and the overall strength only reaches its optimal level after all the water in the system has evaporated. However, under conventional raw materials and proportions, the evaporation of free water in the system is a lengthy process, sometimes exceeding 24 hours. To overcome the problems of slow water evaporation and long traffic opening times in traditional slurry mixtures, this invention introduces an organic-inorganic hybrid flocculant component based on steel slag-based active micro-powder. This component's characteristic is that when the slurry mixture is formed, the flocculant component complexes with the micro-powder, achieving rapid separation of water and powder in the slurry. While basically meeting the water requirements for the hydration reaction, it maximizes water evaporation and significantly shortens the mixture forming time. Simultaneously, the flocculant component guides the cementitious products such as hydrated calcium silicate and hydrated calcium aluminate formed by the water reaction of the steel slag-based active micro-powder to form asphalt slurry, which adheres to the surface of the steel slag aggregate, generating bonding strength.
[0010] Furthermore, based on the use of high-performance modified emulsified asphalt, this invention employs an epoxy material system capable of gradient reactions in water or high-humidity environments. Ketoimine, as a latent epoxy curing agent, hydrolyzes in the presence of moisture and water in the emulsified asphalt to generate ketones and primary amines. The primary amines react with epoxy groups to form chains with (-NH-) groups, and the secondary amine groups continue to react with epoxy groups to generate an epoxy-cured cementitious matrix. This invention premixes diethylenetriamine, tartaric acid, citric acid, and steel slag aggregate. Tartaric acid and citric acid are water-soluble and acidic, accumulating on the surface of the steel slag aggregate. Under the influence of the acidic protons of diethylenetriamine, tartaric acid, and citric acid, ketoneimine undergoes accelerated hydrolysis, rapidly reacting with the epoxy resin to generate a cured product, thus enhancing the interfacial bonding strength of the aggregate. Simultaneously, the acidic nature of the emulsified asphalt (pH ≤ 3) also accelerates the hydrolysis of ketoneimine, promoting the reaction process, and the resulting cured product enhances the cohesiveness of the asphalt mixture. Furthermore, this invention selects two types of epoxy curing agents, T-31 and Schiff bases, to further enhance the performance of the system. T31 is a typical Mannesian addition polyamine that cures bisphenol A type epoxy resin at low temperatures and can be used in environments with 80% humidity and underwater. Under the same conditions, the product obtained has a curing shrinkage rate that is 1 / 3 that of ethylenediamine, higher bond strength than ethylenediamine, excellent chemical corrosion resistance, and the reaction can continue. To enhance the cohesion of the asphalt mixture, Schiff bases are selected as curing agents. Especially when the Schiff base n=3, the reaction rate is faster, the cured product has higher hardness, its flexural strength can reach over 6MPa, and its impact strength is 3.7kJ / m. -2 The three types of curing agents, under the action of their respective accelerators, continuously undergo chemical reactions, progressively improving the system's bonding capacity and interfacial adhesion during the cold asphalt mixture curing process. Simultaneously, the resulting three-dimensional interwoven network structure works synergistically with the asphalt materials, endowing the mixture with stronger temperature stability, wear resistance, and anti-stripping ability.
[0011] Preferably, the mass ratio of the epoxy resin, ketimine, diethylenetriamine, T-31 curing agent, ethanol, Schiff base and trimethylbenzylammonium hydroxide is (60~75):(10~15):(0.2~0.3):(8~12):(0.8~1.0):(6~10):(0.3~0.5).
[0012] Preferably, the mass ratio of tartaric acid, citric acid and epoxy resin is (0.5~1.0):(0.5~1.0):(60~75).
[0013] Preferably, the active micro powder comprises steel slag powder, carbide slag, and Belite sulfoaluminate cement. More preferably, the mass ratio of the steel slag powder, carbide slag, and Belite sulfoaluminate cement is (8~12):1:(1~3).
[0014] Preferably, the hybrid flocculant composition includes chitin, potassium aluminum sulfate dodecahydrate, polyacrylamide, and polyaluminum chloride. More preferably, the mass ratio of chitin, potassium aluminum sulfate dodecahydrate, polyacrylamide, and polyaluminum chloride is (1.0~2.0):(1.5~2.0):(2.0~3.0):(2.5~3.0).
[0015] Preferably, the modified emulsified asphalt has a solid content ≥65%, a softening point of evaporation residue ≥80℃, a ductility of 5℃ ≥50cm, an elastic recovery of ≥85% at 25℃, a dynamic viscosity of ≥55000Pa•s at 60℃, and a pH value ≤3.
[0016] Current mainstream preventative maintenance technologies have significant shortcomings: the performance of emulsified asphalt, the binder material, is poor, easily softening at high summer temperatures (road surface temperatures exceeding 60°C) and cracking at low winter temperatures, with insufficient cohesiveness, leading to early-stage defects such as spalling and interlayer delamination. Therefore, this invention uses high-performance modified emulsified asphalt, and its performance indicators, such as softening point, low-temperature ductility, dynamic viscosity at 60°C, and elastic recovery at 25°C, are all significantly superior to traditional slow-cracking, fast-setting cationic emulsified asphalt. It exhibits excellent high-temperature stability and low-temperature viscoelasticity, ensuring reliable adhesion, improved cohesiveness, and enhanced binding capacity.
[0017] Another object of the present invention is to provide a method for preparing the steel slag cold-mix asphalt wear course mixture, comprising the following steps:
[0018] S1. Determine the volume percentage of each grade of material according to the gradation range of the synthetic ore; then, based on the gross volume relative density of each ore component, convert the volume percentage of each ore into a mass percentage, and calculate the weight parts of steel slag aggregate, manufactured sand and active micro powder respectively.
[0019] S2. After mixing diethylenetriamine, T-31 curing agent, tartaric acid and citric acid, add steel slag aggregate and mix to obtain steel slag aggregate for later use;
[0020] S3. The active micro powder is soaked in a mixed solution of ether and kerosene, and then a hybrid flocculant is added to form a suspension. After shearing, mixing and drying, the active micro powder is obtained for later use.
[0021] S4. Mix the manufactured sand with the steel slag aggregate obtained in step S2 and the active micro powder obtained in step S3 to obtain the synthetic mineral material;
[0022] S5. Add the ketimine and Schiff base into the epoxy resin sequentially, stir thoroughly until homogeneous, and set aside.
[0023] S6. Dissolve trimethylbenzylammonium hydroxide and ethanol in water, and then wet and mix with the synthetic ore obtained in step S4 for later use;
[0024] S7. After thoroughly mixing the modified emulsified asphalt with the material prepared in step S5, add it to the material obtained in step S6 and mix thoroughly to obtain a high-viscosity, anti-skid, and wear-resistant steel slag cold-mix asphalt wear course mixture.
[0025] Steel slag has a porous structure and a large specific surface area. Its specific gravity is about 1.3 times that of basalt aggregate. When designing mix proportions, the gradation design theory used for the aggregates is the volumetric design theory, and the admixture ratio of each grade of aggregate is a volume ratio, while the screening percentage is a volume percentage. However, in my country's engineering applications of asphalt mixtures, the mass method is usually used for production to facilitate this process. When the densities of the aggregates are consistent or not significantly different, the error produced by the mass method can be ignored. However, when different types of aggregates are used and the density differences between them are large, a corresponding volume-mass conversion should be performed to obtain the actual admixture mass ratio of different aggregates. This invention designs a conversion method between volume ratio and mass ratio, solving the problem of gradation variation.
[0026] In step S2 of this invention, diethylenetriamine, tartaric acid, citric acid, and steel slag aggregate are premixed. Tartaric acid and citric acid are water-soluble and acidic, accumulating on the surface of the steel slag aggregate. Ketoimine, under the influence of the acidic protons of diethylenetriamine, tartaric acid, and citric acid, undergoes accelerated hydrolysis and rapidly reacts with epoxy resin to generate a cured product that enhances the interfacial bonding strength of the aggregate. Furthermore, in step S3, active micropowder is soaked in a mixed solution of ether and kerosene, and then a hybrid flocculant is added. After shearing, mixing, and drying, the active micropowder is obtained. When the slurry mixture is formed, the flocculant can complex the micropowder, achieving rapid separation of water and powder in the slurry. While basically meeting the water requirements for the hydration reaction, it maximizes the acceleration of water evaporation, significantly shortening the mixture forming time. Simultaneously, the flocculant guides the cementitious products such as hydrated calcium silicate and hydrated calcium aluminate formed by the water reaction of the steel slag-based active micropowder to form asphalt slurry, which adheres to the surface of the steel slag aggregate, generating bonding strength.
[0027] Compared with the prior art, the advantages of the present invention are:
[0028] (1) The present invention uses steel slag aggregate with high wear resistance, high strength and good angularity as the skeleton structure material of cold-laid anti-slip wear layer, which can significantly improve the wear resistance of wear layer.
[0029] (2) The present invention uses active micro powder instead of mineral powder as filler. Without changing the mineral gradation curve, the active micro powder will react with water to generate hydration cementitious products, which can improve the microstructure and interface deformation of the mixture mortar, and form a three-dimensional skeleton network structure with greater stiffness together with asphalt and aggregate, effectively improving the cohesion, rutting resistance, adhesion and wear resistance of the mixture.
[0030] (3) In order to overcome the problems of slow water evaporation and long traffic opening time of traditional slurry mixtures, this invention introduces an organic-inorganic hybrid flocculant component based on steel slag-based active micro powder. The characteristic of this component is that when the slurry mixture is formed, the flocculant component complexes the micro powder, realizing the rapid separation of water and powder in the slurry. Under the condition of basically meeting the water requirements of the hydration reaction, it accelerates water evaporation to the maximum extent and significantly shortens the forming time of the mixture. At the same time, under the action of the flocculant component, the steel slag-based active micro powder rapidly complexes and aggregates to undergo a hydration reaction, forming cementitious products such as hydrated calcium silicate and hydrated calcium aluminate, which together with asphalt form asphalt slurry and adhere to the surface of steel slag aggregate, generating bonding strength.
[0031] (4) Based on the use of high-performance modified emulsified asphalt, this invention adopts an epoxy material system capable of gradient reaction in water or high humidity environments. Three types of curing agents, namely ketimine, T-31 and Schiff base, are used to perform gradient curing of epoxy resin, which improves the bonding ability and interfacial adhesion of the system in stages. At the same time, the three-dimensional interwoven network structure formed works synergistically with the asphalt material to give the mixture stronger temperature stability, wear resistance and anti-stripping ability. Furthermore, by premixing diethylenetriamine, T31 curing agent, tartaric acid, citric acid and steel slag aggregate, the epoxy material is preferentially adsorbed into the open structure and surface texture of the steel slag aggregate. After reacting with epoxy resin, the resulting epoxy solidified body can effectively enhance the interfacial bonding strength of the steel slag aggregate and improve the wear resistance of the mixture system.
[0032] (5) The present invention converts the volume percentage of each mineral material into a mass percentage based on the gross volume relative density of each mineral material component, thus solving the problem of gradation variation. Detailed Implementation
[0033] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0034] The high-viscosity, anti-slip, and wear-resistant steel slag cold-mix asphalt wear course mixture of the present invention comprises the following components in parts by weight: 8-11 parts modified emulsified asphalt, 35-55 parts steel slag aggregate, 30-50 parts manufactured sand, 6-9 parts active micro powder, 6-10 parts thickening and modifying material, 0.3-1.5 parts hybrid flocculant component, and 5-8 parts water;
[0035] The tackifying and modifying materials include epoxy resin, ketimine, diethylenetriamine, tartaric acid, citric acid, T-31 curing agent, ethanol, Schiff base, and trimethylbenzylammonium hydroxide.
[0036] Among them, the solid content of modified emulsified asphalt is ≥65%, the softening point of evaporation residue is ≥80℃, the ductility at 5℃ is ≥50cm, the elastic recovery at 25℃ is ≥85%, the dynamic viscosity at 60℃ is ≥55000Pa•s, and the pH value is ≤3.
[0037] The steel slag aggregate has a crushing value ≤18%, Los Angeles abrasion loss ≤22%, polishing value (BPN) ≥43, free calcium oxide content ≤3.0%, water immersion expansion rate ≤2%, and metallic iron ≤2%. Other technical indicators must meet the requirements of the "Technical Specification for Construction of Highway Asphalt Pavement" (JTG F40-2004). The sieve passing rate is shown in Table 1.
[0038] Table 1. Screen passing rate of steel slag aggregate
[0039]
[0040] The manufactured sand is made from crushed limestone, with a sand equivalent of ≥70%, a methylene blue value of ≤2.5, and an angularity (flow time) of ≥30s. Other technical indicators must meet the requirements of the "Technical Specification for Construction of Asphalt Pavement of Highway" (JTG F40-2004). The sieve passing rate is shown in Table 2.
[0041] Table 2. Sieve passing rate of manufactured sand
[0042]
[0043] In some embodiments, the mass ratio of the epoxy resin, ketimine, diethylenetriamine, T-31 curing agent, ethanol, Schiff base and trimethylbenzylammonium hydroxide is (60~75):(10~15):(0.2~0.3):(8~12):(0.8~1.0):(6~10):(0.3~0.5).
[0044] In some embodiments, the mass ratio of tartaric acid, citric acid and epoxy resin is (0.5~1.0):(0.5~1.0):(60~75).
[0045] In some embodiments, the active micro powder comprises steel slag powder, carbide slag, and Belite sulfoaluminate cement in a mass ratio of (8~12):1:(1~3).
[0046] Among them, the steel slag powder meets the technical requirements of "Steel Slag Powder" (GB / T 28293-2012); the main component of calcium carbide slag is calcium hydroxide, with a content of not less than 60%; Belite sulfoaluminate cement meets the technical requirements of (T / CBMF 253-2024); and the specific surface area of all powders is not less than 380 m². 2 / kg.
[0047] In some embodiments, the hybrid flocculant component comprises chitin, potassium aluminum sulfate dodecahydrate, polyacrylamide, and polyaluminum chloride in a mass ratio of (1.0~2.0):(1.5~2.0):(2.0~3.0):(2.5~3.0).
[0048] In the following examples and comparative examples, the epoxy resin is liquid bisphenol A epoxy resin, which may be at least one of E-41, E-44, and E-51; the ketimine is prepared from triethylenetetramine and methyl isobutyl ketone; the T-31 curing agent is a phenolic amine epoxy curing agent, a brownish-red viscous liquid with an amine value of 460~480 KOH / mg; the Schiff base is prepared from lactams or their polymers with oxides or hydroxides of alkali metals, wherein the lactam may be one of laurolactam, deuterolactam, heptanolactam, or pyrrolidone lactam, with the structural formula [insert structural formula here]. , where n is 3.
[0049] In some embodiments, a method for preparing the steel slag cold-mix asphalt wear course mixture is provided, comprising the following steps:
[0050] S1. Determine the volume percentage of each grade of material according to the gradation range of the synthetic ore; then, based on the gross volume relative density of each ore component, convert the volume percentage of each ore into a mass percentage, and calculate the weight parts of steel slag aggregate, manufactured sand and active micro powder respectively.
[0051] S2. After mixing diethylenetriamine, T-31 curing agent, tartaric acid and citric acid, add steel slag aggregate and mix to obtain steel slag aggregate for later use;
[0052] S3. The active micro powder is soaked in a mixed solution of ether and kerosene, and then a hybrid flocculant is added to form a suspension. After shearing, mixing and drying, the active micro powder is obtained for later use.
[0053] S4. Mix the manufactured sand with the steel slag aggregate obtained in step S2 and the active micro powder obtained in step S3 to obtain the synthetic mineral material;
[0054] S5. Add the ketimine and Schiff base into the epoxy resin sequentially, stir thoroughly until homogeneous, and set aside.
[0055] S6. Dissolve trimethylbenzylammonium hydroxide and ethanol in water, and then wet and mix with the synthetic ore obtained in step S4 for later use;
[0056] S7. After thoroughly mixing the modified emulsified asphalt with the material prepared in step S5, add it to the material obtained in step S6 and mix thoroughly to obtain the final product.
[0057] In some specific embodiments, step S1 is as follows:
[0058] (1) Carry out the gradation design of mineral materials. Based on the screening results of steel slag aggregate, manufactured sand and active micro powder, determine the mixing volume ratio of each grade of material according to the gradation range in Table 3.
[0059] Table 3. Gradation range of synthetic minerals
[0060]
[0061] (2) The conversion formula for the mass ratio of each grade of aggregate in the design of synthetic mineral aggregate is as follows:
[0062] Table 4. Synthetic Mineral Gradation Design
[0063]
[0064] Formula 1:
[0065] Gv1+Gv2+Gv3+Jv+Hv=100;
[0066] Formula 2:
[0067] q 总 =Gv1*Gp1+Gv2*Gp2+Gv3*Gp3+Jv*Jp+Hv*Hp;
[0068] Formula 3:
[0069] Gq1 = (Gv1 * Gp1) / q 总 *100;
[0070] Gq 2= (Gv2*Gp2) / q 总 *100;
[0071] Gq3 = (Gv3 * Gp3) / q 总 *100;
[0072] Jq = (Jv * Jp) / q 总 *100;
[0073] Hq = (Hv * Hp) / q 总 *100;
[0074] (3) Convert the volume ratio of each material in (1) into the mass ratio according to the conversion formula in (2), and calculate the mass fraction of steel slag coarse aggregate, manufactured sand and active micro powder respectively.
[0075] Example 1
[0076] This embodiment provides a method for preparing a high-viscosity, anti-skid, and wear-resistant steel slag cold-mix asphalt wear course mixture, including the following steps:
[0077] S1. Determine the volume percentage of each grade of material according to the gradation range of the aggregates in Table 3; then, based on the gross volume relative density of each component of the aggregates, convert the volume percentage of each aggregate into a mass percentage, and calculate the weight fractions of steel slag aggregate, manufactured sand, and activated micro powder respectively. The specific details before and after conversion are shown in Table 5:
[0078] Table 5. Synthetic mineral aggregate gradation design of Example 1
[0079] S2. After thoroughly mixing 0.018 parts of diethylenetriamine, 0.8 parts of T-31 curing agent, 0.05 parts of tartaric acid and 0.05 parts of citric acid, add the steel slag aggregates of each grade (6.8 parts for 8~10mm, 11.3 parts for 5~8mm, and 39.5 parts for 3~5mm) and mix thoroughly until each component is evenly adhered to the surface of the steel slag to obtain a steel slag aggregate premix for later use.
[0080] S3. Weigh out steel slag powder, carbide slag, and Belite sulfoaluminate cement in a mass ratio of 10:1:2, mix them evenly to obtain active micro powder; then soak the active micro powder (7.6 parts) in a mixed solution of ether and kerosene (mass ratio 1:1), and then add chitin (0.076 parts), potassium aluminum sulfate dodecahydrate (0.114 parts), polyacrylamide (0.228 parts), and polyaluminum chloride (0.19 parts) in sequence to form a suspension. Use a shear emulsifier to fully shear and mix the above suspension, and dry it to use as an active micro powder filler for later use;
[0081] S4. The steel slag coarse aggregate premix obtained in step S2, the active micro powder filler obtained in step S3, and the manufactured sand (34.8 parts) are mixed to obtain the synthetic mineral material;
[0082] S5. Add ketimine (1.2 parts) and Schiff base (0.72 parts) to epoxy resin (6.0 parts) in sequence, stir thoroughly and set aside;
[0083] S6. Dissolve 0.04 parts of trimethylbenzylammonium hydroxide and 0.07 parts of ethanol in 7 parts of water, and mix with the synthetic ore obtained in step S4 for later use;
[0084] S7. After thoroughly mixing the modified emulsified asphalt (10 parts) with the material prepared in step S5, add it to the material obtained in step S6 and mix thoroughly to obtain a high-viscosity, anti-skid, and wear-resistant steel slag cold-mix asphalt wear layer mixture.
[0085] Comparative Example 1
[0086] The preparation method of the high-viscosity, anti-skid, and wear-resistant steel slag cold-mix asphalt wear course mixture in this comparative example includes the following steps:
[0087] S1. Determine the volume percentage of steel slag aggregate, manufactured sand, and activated micro powder according to the aggregate gradation range in Table 3, as shown in Table 6:
[0088] Table 6. Synthetic mineral aggregate gradation design for Comparative Example 1
[0089]
[0090] S2. After thoroughly mixing 0.018 parts of diethylenetriamine, 0.8 parts of T-31 curing agent, 0.05 parts of tartaric acid and 0.05 parts of citric acid, add each grade of steel slag aggregate (6 parts for 8~10mm, 10 parts for 5~8mm, and 35 parts for 3~5mm) and mix thoroughly until each component is evenly adhered to the surface of the steel slag to obtain a steel slag aggregate premix for later use.
[0091] S3 is the same as in Example 1;
[0092] S4. Mix the steel slag coarse aggregate premix obtained in step S2, the active micro powder filler obtained in step S3, and manufactured sand (40 parts) to obtain synthetic mineral material;
[0093] Steps S5-S7 are the same as in Example 1;
[0094] Compared with Example 1, this comparative example omits the step of converting the volume percentage of each mineral material into a mass percentage.
[0095] Comparative Example 2
[0096] The preparation method of the high-viscosity, anti-skid, and wear-resistant steel slag cold-mix asphalt wear course mixture in this comparative example is basically the same as that in Example 1, except that the active micro powder is replaced with an equal amount of mineral powder.
[0097] Comparative Example 3
[0098] The preparation method of the high-viscosity, anti-slip, and wear-resistant steel slag cold-mix asphalt wear layer mixture in this comparative example is basically the same as that in Example 1. The only difference is that step S3 is: weigh steel slag powder, carbide slag, and Belite sulfoaluminate cement in a mass ratio of 10:1:2 and mix them together to obtain active micro powder filler; that is, compared with Example 1, this comparative example omits the hybrid flocculation component.
[0099] Comparative Example 4
[0100] The preparation method of the high-viscosity, anti-skid, and wear-resistant steel slag cold-mix asphalt wear course mixture in this comparative example is basically the same as that in Example 1. The only difference is that T-31 curing agent and ethanol are omitted, the weight parts of ketimine are adjusted to 2.0 parts, and the weight parts of diethylenetriamine are adjusted to 0.088 parts.
[0101] Comparative Example 5
[0102] The preparation method of the high-viscosity, anti-skid, and wear-resistant steel slag cold-mix asphalt wear course mixture in this comparative example is basically the same as that in Example 1, except that ketimine and diethylenetriamine are omitted, the weight of T-31 curing agent is adjusted to 2.0 parts, and the weight of ethanol is adjusted to 0.088 parts.
[0103] Comparative Example 6
[0104] The preparation method of the high-viscosity, anti-skid, and wear-resistant steel slag cold-mix asphalt wear course mixture in this comparative example is basically the same as that in Example 1, except that Schiff base and trimethylbenzylammonium hydroxide are omitted, the weight parts of ketimine are adjusted to 8.4 parts, and the weight parts of diethylenetriamine are adjusted to 0.058.
[0105] Comparative Example 7
[0106] The preparation method of the high-viscosity, anti-skid, and wear-resistant steel slag cold-mix asphalt wear course mixture in this comparative example is basically the same as that in Example 1, with the only difference being:
[0107] Step S1 is the same as in Example 1;
[0108] Step S2 is changed to: Mix the steel slag aggregates of each grade (6.8 parts for 8~10mm, 11.3 parts for 5~8mm, and 39.5 parts for 3~5mm) evenly to obtain steel slag aggregates for later use;
[0109] Step S5 is changed to: mixing ketimine (1.2 parts), T-31 curing agent (0.8 parts), and Schiff base (0.72 parts) into epoxy resin (6.0 parts) in sequence, stirring thoroughly and evenly, and set aside;
[0110] Step S6 is changed to: dissolve trimethylbenzylammonium hydroxide (0.04 parts), ethanol (0.07 parts), diethylenetriamine (0.018 parts), tartaric acid (0.05 parts) and citric acid (0.05 parts) in water (7 parts), and wet and mix with the synthetic ore obtained in step S4 for later use.
[0111] Compared to Example 1, this comparative example did not premix diethylenetriamine, T-31 curing agent, tartaric acid, citric acid and steel slag aggregate.
[0112] According to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011), relevant tests were carried out on the mixtures prepared in the examples and comparative examples. The performance test results are shown in Table 7.
[0113] Table 7 Performance test results of the mixture
[0114] Note: The initial stage of health preservation in the table refers to 2 hours of health preservation under conditions of 25℃ temperature and 70% humidity;
[0115] As can be seen from the data in Table 7, the mixture prepared by this invention has a short demulsification time, high cohesion, and low wet wheel wear loss in the initial stage, 1 hour, and 6 days, indicating that the mixture has excellent wear resistance and cohesive properties.
[0116] By comparing Example 1 and Comparative Example 1, it can be found that Comparative Example 1 omits the step of converting the volume percentage of each aggregate into a mass percentage. The cohesion of the prepared mixture is reduced, and the amount of sand adhering to the load wheel and the width change rate of the wheel rut deformation test are increased. This indicates that the total volume of the synthetic aggregate in the unconverted mixture is reduced under the same mass, resulting in an additional increase in the amount of asphalt used by mass measurement. This is manifested in the obvious case of excessive asphalt-aggregate ratio and excessive asphalt content.
[0117] By comparing Example 1 and Comparative Example 2, it can be found that when the active micro powder was replaced with an equal amount of mineral powder in Comparative Example 2, the demulsification time was longer and the initial wear resistance of the mixture did not change significantly. However, the wet wheel wear value after immersion in water at 25°C for 6 days increased by more than several times, indicating that the gelation products generated by the hydration gelation reaction of the active micro powder within 6 days of age improved the wear resistance of the mixture.
[0118] By comparing Example 1 and Comparative Example 3, it can be found that Comparative Example 3 omits the hybrid flocculant component, resulting in a longer demulsification time. At the same time, the wear loss in the early stage of curing increased by 37.5%, and the cohesion of the mixture decreased, indicating that the complexation effect of the flocculant component has a significant impact on the water overflow effect of the system.
[0119] By comparing Example 1 and Comparative Examples 4-6, it can be found that when any one of the curing agents, ketimine, T-31 curing agent, and Schiff base is omitted, the wet wheel wear loss of the mixture increases significantly at the initial stage, 1 hour, and 6 days, and the cohesion decreases significantly. At the same time, the width change rate of the wheel rut deformation test increases, and the amount of sand adhering to the load wheel increases. This indicates that only under the gradient curing of ketimine, T-31 curing agent, and Schiff base can the cohesive strength, wear resistance, and deformation resistance of the system be effectively improved.
[0120] By comparing Example 1 and Comparative Example 7, it can be found that Comparative Example 7 did not premix diethylenetriamine, tartaric acid, citric acid and steel slag aggregate. The wet wheel abrasion value of the mixture after soaking in water at 25°C for 1 hour and 6 days increased. This indicates that by premixing diethylenetriamine, tartaric acid, citric acid and steel slag aggregate, the interfacial bonding strength of the aggregate was enhanced, the adhesion to asphalt mortar was increased, and the wear resistance of the mixture system was improved.
[0121] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A high-viscosity, anti-slip, and wear-resistant steel slag cold-mix asphalt wear course mixture, characterized in that, The components include the following parts by weight: 8-11 parts modified emulsified asphalt, 35-55 parts steel slag aggregate, 30-50 parts manufactured sand, 6-9 parts active micro powder, 6-10 parts thickening and modifying material, 0.3-1.5 parts hybrid flocculant component, and 5-8 parts water. The tackifying and modifying materials include epoxy resin, ketimine, diethylenetriamine, tartaric acid, citric acid, T-31 curing agent, ethanol, Schiff base, and trimethylbenzylammonium hydroxide.
2. The cold-mix asphalt wear course mixture with steel slag according to claim 1, characterized in that, The mass ratio of the epoxy resin, ketimide, diethylenetriamine, T-31 curing agent, ethanol, Schiff base and trimethylbenzylammonium hydroxide is (60~75):(10~15):(0.2~0.3):(8~12):(0.8~1.0):(6~10):(0.3~0.5).
3. The cold-mix asphalt wear course mixture with steel slag according to claim 1, characterized in that, The mass ratio of tartaric acid, citric acid and epoxy resin is (0.5~1.0):(0.5~1.0):(60~75).
4. The cold-mix asphalt wear course mixture with steel slag according to claim 1, characterized in that, The active micro powder includes steel slag powder, carbide slag, and Belite sulfoaluminate cement.
5. The cold-mix asphalt wear course mixture with steel slag according to claim 4, characterized in that, The mass ratio of the steel slag powder, carbide slag and Belite sulfoaluminate cement is (8~12):1:(1~3).
6. The cold-mix asphalt wear course mixture with steel slag according to claim 1, characterized in that, The hybrid flocculant components include chitin, potassium aluminum sulfate dodecahydrate, polyacrylamide, and polyaluminum chloride.
7. The cold-mix asphalt wear course mixture with steel slag according to claim 6, characterized in that, The mass ratio of chitin, potassium aluminum sulfate dodecahydrate, polyacrylamide, and polyaluminum chloride is (1.0~2.0):(1.5~2.0):(2.0~3.0):(2.5~3.0).
8. The cold-mix asphalt wear course mixture with steel slag according to claim 1, characterized in that, The modified emulsified asphalt has a solid content ≥65%, a softening point of evaporation residue ≥80℃, a ductility of 5℃ ≥50cm, an elastic recovery of ≥85% at 25℃, a dynamic viscosity of ≥55000Pa•s at 60℃, and a pH value ≤3.
9. The method for preparing the steel slag cold-mix asphalt wearing course mixture according to any one of claims 1 to 8, characterized in that, Includes the following steps: S1. Determine the volume percentage of each grade of material according to the gradation range of the synthetic ore; then, based on the gross volume relative density of each ore component, convert the volume percentage of each ore into a mass percentage, and calculate the weight parts of steel slag aggregate, manufactured sand and active micro powder respectively. S2. After mixing diethylenetriamine, T-31 curing agent, tartaric acid and citric acid, add steel slag aggregate and mix to obtain steel slag aggregate for later use; S3. The active micro powder is soaked in a mixed solution of ether and kerosene, and then a hybrid flocculant is added to form a suspension. After shearing, mixing and drying, the active micro powder is obtained for later use. S4. Mix the manufactured sand with the steel slag aggregate obtained in step S2 and the active micro powder obtained in step S3 to obtain the synthetic mineral material; S5. Add the ketimine and Schiff base into the epoxy resin sequentially, stir thoroughly until homogeneous, and set aside. S6. Dissolve trimethylbenzylammonium hydroxide and ethanol in water, and then wet and mix with the synthetic ore obtained in step S4 for later use; S7. After thoroughly mixing the modified emulsified asphalt with the material prepared in step S5, add it to the material obtained in step S6 and mix thoroughly to obtain a high-viscosity, anti-skid, and wear-resistant steel slag cold-mix asphalt wear course mixture.
Citation Information
Patent Citations
Cold-laid anti-skid wearing layer material and preparation method thereof
CN117623677A